Relationship between voluntary disclosures & ownership structure : evidence from Singapore. - Chua, Julie Ching Ching. (2008)
This study investigates the relationship between ownership structure and the extent of voluntary disclosures of 203 companies listed on the SGX. In addition, we consider whether proprietary cost and regulation moderate the relationship between the level of voluntary disclosure and ownership structure.